Radiological response to nivolumab in patients with hepatocellular carcinoma: A multicenter analysis of real-life practice. Issue 135 (February 2021) - Rimola, Jordi; Da Fonseca, Leonardo G.; Sapena, Víctor; Perelló, Christie; Guerrero, Antonio; Simó, Maria Torner; Pons, Monica; De La Torre-Aláez, Manuel; Márquez, Laura; Calleja, José Luis; Lledó, José Luis; Varela, Maria; et al.
Highlights: Imaging findings at different timepoints for HCC treated with nivolumab vary between patients and within patients. The possibility of pseudoprogression must be taken into account when interpreting radiological progression. Applying iRECIST rules will enable patients with pseudoprogression to benefit from continued treatment. Abstract: Background and aims: Immune-checkpoint inhibitors are effective in many advanced tumors. However, there is scarce information regarding the radiological response to these agents in hepatocellular carcinoma outside clinical trials. We aimed to describe the radiological response in a retrospective cohort of hepatocellular carcinoma patients treated with nivolumab and to analyze the radiological evolution according to tumor response at first post-treatment radiological assessment. Methods: We reviewed pre-treatment and post-treatment images (CT or MRI) obtained at different time-points in patients with hepatocellular carcinoma treated with nivolumab outside clinical trials at seven Spanish centers, assessing the response according to RECIST 1.1 and iRECIST and registering atypical responses. We also analyzed the imaging findings on subsequent assessments according to tumor status on the first posttreatment imaging assessment. Results: From the 118 patients with hepatocellular carcinoma treated with nivolumab, we finally analyzed data from 31 patients (71 % Child-Pugh A; 74 % BCLC-C). Median follow-up was 8.39 months [IQR 5.00–10.92]; median overall survival was 12.82 months (95 %CI 10.92–34.79). According to RECIST 1.1, the objective response rate was 16 % and according to iRECIST, the objective response rate was 22.6 %. Findings at the first post-treatment assessment varied, showing stable disease in 44.8 % of patients; findings during follow-up also varied widely, including 4 hyperprogressions and 3 pseudoprogressions. Conclusion: Imaging findings during nivolumab treatment are heterogeneous between and within patients. Progression of disease does not always signify treatment failure, and surrogate end-points may not reflect survival outcomes, making the management of hepatocellular carcinoma patients under immunotherapy challenging.